Comparison of autoecological indicators in growth dynamics of Festuca dolichophylla (Presl, 1830) and Festuca humilior (Nees & Meyen, 1841) - Trillo Zárate, Fritz Carlos (2020)
The aim of this study was to compare the growth, biomass accumulation, tillering dynamics and water behavior of Festuca dolichophylla (Presl, 1830) (fedo) and Festuca humilior (Nees y Meyen, 1841) (fehu). The study was carried out in grasslands of good condition in the Peruvian highlands at an altitude of 4186 m. The model included species and month as fixed effects, and age post-plating as a random effect. fedo evidenced a greater height to the flag leaf with 29.66±0.56 cm and volume of grass with 993.88±44.34 cm3, while fehu evidenced a greater proportion of flowering with 35.71±1.84%. Both species had a similar quantity of basal tillers. In March-2016 the highest peak of volumetric soil moisture (20 cm) with 57.37±0.78% was evidenced, while in September 2016 it was the lowest peak with 13.86±0.83%. In December 2016, the highest transpiration peaks were evident with 92-95 mmol m2- s-1, while the lowest peak was in July 2016 with 24-27 mmol m2- s-1. fedo had the greatest growth and accumulation of biomass, possibly its adaptive strategy is space occupation. fehu had the highest flowering rate, where persistent flowering is possibly because its adaptive strategy. The transpiration rate in fedo and fehu was similar and lower than other species in semi-arid grasslands, proving to be more efficient in the adaptive strategy of water use.